Exploring the versatility of Magnetic Relaxation Switching (MRS) and CRISPR-based biosensors for the detection of foodborne pathogens; a comprehensive review - Hiya Borah; Omar Bashir; Prashant Anil Pawase; Imdad Ul Hoque Mondal; Szilvia Várallyay; Diána Ungai; Béla Kovács (Applied Food Research)
Food-borne pathogens such as E. coli., Salmonella, Listeria monocytogenes, Campylobacter jejuni are the common ones that pose a significant threat to human health and therefore require quick accurate affordable detection of food pathogens. Traditional pathogen identification procedures in foods are laborious and expensive and require specialized equipments. Magnetic Relaxation Switching (MRS) biosensors, which work by monitoring changes on dispersion, aggregation, or concentration change of magnetic nanoparticle (MNPs), have emerged as an potential alternative. Therefore, MNPs have gained wide applications due to the typical magnetic properties that may efficiently enhance the target, separate, and capture with high sensitivity. However, traditional MRS biosensors are often insensitive and unstable. The review, therefore, focuses on the latest development of CRISPR-Cas12a-assisted MRS biosensors for improving food safety monitoring. The CRISPR-Cas12a system enhances pathogen detection by recognizing and cleaving target sequence with high precision. Lastly, the review sums up the improvements of different biosensors in comparison with conventional biosensors and shows the use of MNPs in the identification process of various pathogens.